Assessing experimental apparatus for sheet metal electromagnetic forming process analysis. Issue 12 (10th September 2022) - Paese, E.; Geier, M.; Homrich, R. P.; Rossi, Rodrigo; Rosa, Pedro
ABSTRACT: Aiming to contribute to the development of electromagnetic forming (EMF) technology, this study proposes the design and development of an affordable EMF apparatus intended to be used in laboratory facilities. While commercial solutions for EMF machines are equipped with high voltage pulse capacitors and solid-state switches, this paper focuses on affordable components, such as low-voltage electrolytic capacitors, high-current switches, and the tool coil. The apparatus is evaluated through simulations, using an in-house mathematical model, and experiments considering the characterization and assessment of the pulse unit by means of the current frequency, the magnetic flux density, and the distribution of the pressure. The achieved simulated results for the discharge current, considering coupled and uncoupled metal sheet conditions, coincide with the measurements. The proposed main discharge switch effectively withstands both high discharge current peak and rise rate. In addition, a comparative evaluation of the discharge current oscillation frequency is presented, resulting in differences in terms of significant frequency and Fourier analysis of up to +32% and −15%, respectively, when compared to the formula of series RLC circuit. The proposed apparatus is useful for performing experiments, which can assist in analyzing process parameters and, consequently, aid to validating physical hypotheses and mathematical models.